Clinical definition and diagnostic criteria for sarcopenia - Jun Udaka; Norio Fukuda; Hideki Yamauchi; Keishi Marumo (Japanese Society of Physical Fitness and Sports Medicine, 2014)
The occurrence of sarcopenia and muscular dystrophy with aging has attracted attention. Many factors are reported as causes of sarcopenia, such as the functional decline of a digestive organ occurring with aging and malnutrition due to a decrease in food intake. Also, a decrease in growth hormone and an increase in cytokines are also considered to be causes of sarcopenia. Meanwhile, the differentiation between sarcopenia and disuse muscle atrophy is not clear. It will be important in future studies to clearly define the differences between sarcopenia and disuse muscle atrophy. Recently, the diagnostic criteria of sarcopenia have been defined according to a large-scale investigation. In the future, an easier sarcopenia diagnostic method should be developed. It is necessary to design specific treatment strategies more closely correlated to the clinical condition of individual patients, because the causes of sarcopenia vary widely. In this review, we summarize the characteristics of the clinical condition, diagnosis, and treatment of sarcopenia.